PPO.51 Pregnancy Outcomes in Major Congenital Heart Disease. (9th June 2014) - Peake, L; Draper, E; Field, D
Abstract : Background: Advances in management have prolonged the life of many patients with major congenital heart disease (CHD). No national guidelines exist for the counselling of expectant parents with an antenatal diagnosis of a major CHD. Methods: All cases of Hypoplastic Left Heart Syndrome (HLHS), Transposition of the Great Arteries (TGA) and Atrio-Ventricular Septal Defect (AVSD), arising in mothers resident in Leicestershire between 01/01/1998 and 31/12/2012, were identified from the East Midlands and South Yorkshire Congenital Anomaly Register (EMSYCAR). Data regarding pregnancy outcome, antenatal detection and chromosomal abnormality was extracted and compared to national data gathered by EUROCAT. Results: 55, 60 and 84 cases of HLHS, TGA and AVSD were identified respectively. Live birth rates (including and excluding chromosomal diagnoses) were consistent with national rates for all conditions. The rate of termination was significantly lower (p-value < 0.05) for cases of HLHS and AVSD in Leicestershire, than the combined rate for all other UK registers. Antenatal detection was 77.36% (95% CI: 66.09–88.63) for HLHS, 51.06% (95% CI: 36.77–65.35) for TGA and 58.22% (95% CI: 47.34–69.10) for AVSD. These meet the 50% FASP targets. Conclusions: In Leicestershire, cases of HLHS and AVSD are significantly less likely to result in termination of pregnancy compared to the UK as a whole. This may be due to differences in the counselling process provided in the region. Research regarding what contributes to parental decision making in these situations is needed. Detailed guidelines on what the counselling process should constitute may reduce the disparity in termination rate.